PATTERN OF CHIP COLOUR SEGREGATION IN SOME CROSSES OF POTATO - Manivel, P.; Pandey, S K; Singh, S V; Kumar, Dinesh (Potato Journal, 2013)
Pattern of chip colour distribution in the progenies of six crosses was studied in the first clonal generation at CPRS, Kufri. Chip colour distribution varied with cross combinations and frequency of getting excellent chip colour (score 1) was very low (1-5%) in these progenies. Clones with acceptable chips colour were obtained from both type of crosses i.e. good x good chipper and good x poor chipper, but the colour score was better in the latter. Cross combinations MP/97-583 x JEX/A-680-16, MP/97-628 x CP 2417 and MP/97-921 x CP 2132 produced higher percent (40%) of clones with lighter chip colour (< 3) and could be exploited for developing varieties for processing.